PENGARUH SISTEM PENYALURAN KREDIT TERHADAP KEPUASAN ANGGOTA CREDIT UNION KARYA MURNI MEDAN - Saragih, Nawary (UNIKA Santo Thomas, 2018)
Credit Union (CU) Karya Murni Medan is a business engaged in lending and receiving deposits. Members of the CU often complain because of the vulnerable process of administering credit until the disbursement phase, resulting in members less satisfied with the credit distribution system set by the CU. From the problem identification, formulated the research problem is